The Analysis of Attitude in Emma Watson’s Feminism Speeches - Sheilla Oktaviani; Rahmawati Sukmaningrum; Arso Setyaji (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
English has become an international language in the world. It becomes tool of communication for many people freely around the world either in spoken or written context, or direct or indirect interaction. One of the reason this phenomenon caused by the development of technology which has been spreading widely around the world. Therefore, it is important for people to learn, especially for English learner to learn deeper about language in both contexts. Data collection of this research used documentary and visual data or document analysis which is suitable to apply since it refers to describe the attitude through English speech which also related to transcript. This research used the ATLAS software. ti 24, this software is useful in assisting the data analysis process of qualitative grounded theory research. And discourse analysis is one of appropriate study often used to analyse language use both in written and spoken context. The study of attitude also take part in analysing the language because language is also related to improve learner’s interpersonal relationship. In this study will shows the relation of language use in society along with the emotional study based on the language use.